Blood-brain barrier function in cerebral malaria and CNS infections in Vietnam. - Brown, H; Chau, T; Mai, N; Day, N; Sinh, D; White, N; Hien, T; Farrar, J; Turner, G (2000)
BACKGROUND: The intraerythrocytic parasite Plasmodium falciparum induces the life-threatening neurologic syndrome of cerebral malaria (CM) from within cerebral blood vessels, without entering the brain parenchyma. OBJECTIVES: 1) To assess the use of CSF as an indicator of specific pathologic processes occurring in the brain during CM; 2) to compare this with other neurologic and infectious diseases to understand the distinct pathogenic features of CM; 3) to test the hypothesis that CM involves a specific functional breakdown of the blood-brain barrier (BBB). METHODS: 1) Radial immunodiffusion assays to detect albumin and IgG in matched plasma and CSF samples as indicators of BBB integrity and intrathecal IgG production; and 2) ELISA for soluble intracellular adhesion molecule-1 and sE-selectin, the cytokines tumor necrosis factor-alpha and transforming growth factor-beta1, and the matrix metalloproteinase MMP-9, to detect cellular activation and inflammatory responses within the brain. RESULTS: Albumin and IgG indices implied only minimal degree of BBB breakdown in a few cases of CM, with most remaining within the normal range. In contrast, cryptococcal, tubercular, and acute bacterial meningitis produced detectable changes in the composition of the CSF and evidence of BBB breakdown. CONCLUSIONS: CM appears to involve only subtle functional changes in BBB integrity with minimal intraparenchymal inflammatory responses compared with other neurologic infections. This focuses attention on local events within and around the cerebral microvasculature in CM, rather than indicating widespread parenchymal disease.